Relationship between Organizational Communication Climate and Interpersonal Conflict Management - Bushra Hassan, Aneela maqsood, Muhammad Naveed Riaz (Pakistan Journal of Psychology, 2011)
Relation between different styles of interpersonal conflict management and dimensions of organizational communication climate was looked into; employing a sample of 160 bank employees. Sample included men and women employees having age range of 27 to 55 years (M=38.07 and SD=1.44) and education ranges from graduation to post graduation. Organizational Communication Climate Inventory developed by Costigan and Schmeidler (2004) and Rahim Organizational Conflict Inventory II (1983) were administered to assess the communication climate within the organizations and different styles of handling interpersonal conflict. The correlation analysis revealed that supportive (r = .41; p < .000) and defensive (r = .32; p < .001) communication climate dimensions showed positive relationship with total scores of conflict management inventory. The results further showed that integrating (r = .44; p< .001), obliging (r = .46; p < .001) and compromising (r = .26; p <.01) styles of handling conflict has significant positive correlation with supportive communication